Biologically active substances of a fungus Phallus impudicus - Лузіна, Д. В. (Problems of Environmental Biotechnology, 2017)
Phallus impudicus due to biologically active substances is a medicinal fungus used in the treatment of a number of serious diseases. It has been established that for the treatment of diseases suitable as mature fungus. Thе integration of this array of knowledge as a scientific complement in research in the field of mycology, pharmacognosy and immunology is recommended.